Information Model for Distance Education Management in Thai Supply Chain - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The aims of this research was to develop and to evaluate information Model for distance education management in Thai supply chain . The samples are ten experts selected by purposive sampling. The data is analysed by means and standardized deviations. The research result shows that the model consists of five elements namely main components, Suppliers, Manufacturer, ,finished product ,Customers, The assessment of information Model for distance education management in Thai supply chain is rated as absolutely appropriate in overall. The rating mean of 3.67 and standard deviation of 0.73, which means that the model is appropriate at the high level which that mean The model to support information system development.